Analisa Pengaruh Kualitas Pelayanan PT Namora Transindo Jaya Terhadap Tingkat Kepuasan Pelanggan Menggunakan Servqual - Samosir, Elen Togu Marito; Zuraidah, Eva (TIN: Terapan Informatika Nusantara, 2022)
Entrepreneurs will try to provide the best service for customers by meeting their needs of customer demands. PT Namora Transindo Jaya has experienced the impact of the COVID-19 pandemic by decreasing orders for goods delivery services, problems that occur in terms of service quality such as damage to goods or packages when received by customers, delivery of goods or packages experiencing delays or delivery of goods and packages that are not right on time. the time, the return of goods that were not sent due to an unclear address, not on time because the sender was informed beyond the service level agreement (SLA), this greatly affects the quality of service. The solution that will be given is to conduct research using the Fuzzy Service Quality method to determine the quality of service from PT Namora Transindo Jaya. The results of the calculation of the overall, the average calculation of the criteria for the gap between expectations and customer perceptions calculated at PT Namora Transindo Jaya results in a customer satisfaction level of 0.21 which means that customer expectations are exceeded which indicates that the better the quality of the company in the eyes of the company. consumer or customer. The attribute that is rated the highest with a gap value of 1.60 is the dimension of empathy, employees do not discriminate between customers and give equal attention, while the worst attribute is with a gap value of -0.58 dimension of assurance , employees always behave friendly, polite and give a smile to customers